USE OF RADIOLOGICAL ANALYSIS FOR CHOOSING OF OPTIMIZED ROOT CANAL OBTURATION TECHNIQUE - Geranin, S.I.; Gasyuk, N.V.; Chernyak, V.V. (World of Medicine and Biology, 2012)
The objectives of this in vitro study were to evaluate three different root canal obturation techniques in respect of the radiographic quality of root canal obturation.In the radiographic evaluation of the obturation quality in the present study, Lateral Condensation technique resulted in the poorest obturation quality, coronally and apically. Many voids were observed in the obturations and thies are directly related to the difficulty of handling with Lateral Condensation technique in the prepared canals.
Keywords: obturation; canals; lateral condensation